Secure Authentication in Document Oriented Database MongoDB - Aggarwal, Palvi (My University, 2014)
Today organizations almost in every industry are being showered with quantities of new information. Along with traditional sources, many more data channels and categories exist. Collection of this vastly large information volume and new assets are known as big data. Tradition Relational databases deals with the structured data, but now a day’s data is in form of graphs, images, audio, videos and text which is either partially structured or completely unstructured. To deal with such type of data NoSQL databases are introduced. MongoDB is document oriented NoSQL database which stores documents as databases. This is schema less databases, which does not need to follow a particular structure. Horizontal scaling, sharding, replica set, high performance capabilities enhance its demand. But there are some security issues in MongoDB. Security is not major concern of 10gen. In this thesis, research has been carried out to find out the security loopholes and to provide secure authentication in database.
ME, CSED
Keywords: MongoDB, NoSQL, Security